2018
DOI: 10.3390/w10070874
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Evaluation of Comprehensive Treatment for Groundwater Overdraft in Quzhou County, China

Abstract: Abstract:In recent years, land subsidence in the plain areas of Hebei Province has caused a tremendous potential safety hazard, and has seriously hindered the social and economic development of Hebei Province. Therefore, the relevant ministries and commissions of China decided to implement comprehensive treatments to restore and protect groundwater in Hebei Province from 2014. This paper evaluates the effect of the comprehensive treatments implemented at Quzhou County in 2014 and 2015. Based on socio-economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Quzhou County (114.9 • E, 36.7 • N, 40 m above sea level) belongs to the prefecture-level city of Handan, located upstream of the Heilonggang River basin in southern Hebei province, which is one of the most affected area in terms of groundwater depletion in the world [34]. Fertilizers are highly used with inefficiency in the study area.…”
Section: Description Of Study Sitementioning
confidence: 99%
“…Quzhou County (114.9 • E, 36.7 • N, 40 m above sea level) belongs to the prefecture-level city of Handan, located upstream of the Heilonggang River basin in southern Hebei province, which is one of the most affected area in terms of groundwater depletion in the world [34]. Fertilizers are highly used with inefficiency in the study area.…”
Section: Description Of Study Sitementioning
confidence: 99%
“…To validate our findings, we compared our calculated groundwater level changes with measured or officially reported data. The calculations indicate that Quzhou's groundwater level fell by 1.25 m between 2010 and 2015, which is within the 0.5-1.7 m range reported elsewhere for the same period (Xu et al, 2018;Wu and Wu, 2020). Moreover, the local government has maintained monitoring data on groundwater level since 2018 (DWRHP, 2019(DWRHP, -2021.…”
Section: Water Resources In Quzhousupporting
confidence: 85%
“…Groundwater accounted for 70% of the water supplied in the county before the local government restricted groundwater withdrawal in 2014 (DWRH, 2021). According to Xu et al (2018), this has caused groundwater overexploitation and induced groundwater overdraft. Additionally, reported that Quzhou's water supply was affected by severe salinization.…”
Section: Research Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Groundwater may contain natural impurities or pollutants regardless of human activity (1). Groundwater is an important water resource and a major factor for maintaining the regional ecological environment, which plays a significant role in ensuring water, food, economic, and ecological security (2). The chemical composition of groundwater is the product of the long-term interaction between groundwater and the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%